Drought Resistance Variation of Mutant of Kenaf KR11 Based on Prolin Accumulation - Rahmi Marsita; Estri Laras Arumingtyas (Natural B, Journal of Health and Environmental Sciences, 2014)
Kenaf is a fiber plants of the family Malvaceae. KR 11 is a high yielding kenaf variety which is resistant to drought stress. Mutations by EMS at several species known to increase resistance to drought stress by accumulation of osmolite. In this research, physiological testing on 5 mutants to determine the effect of the mutation on the drought stress response of kenaf KR 11was conducted. Experiment were done by comparing the physiological accumulation of proline in normal and drought stress conditions. The plants were watered every 3 days for 14 days with 100% of field capacity as normal conditions and 25% field capacity as drought stress. The results showeddifferences inthe pattern ofprolineaccumulationbetweencontrolandmutant in normal and drought stress condition. While control KR11 increased the accumulation on drought condition, mutants showed decreasedprolin content under conditions of stresswith varying decreasing levels. The mostsignificant pattern ofproline accumulationcompared with control, is shownby themutant4and5. Prolin accumulation pattern is controlled by the proline metabolism control genes, P5CS and ProDH and its feedback regulation. Alteration of this pattern is most likely an effect of mutation induction on the mutant sample.